"Spacecraft Reveals Recent Geological Activity on the Moon". Issue 5 (February 2014) - Lesley, Mellinee
Abstract Through a content analysis of 200 "tweets, " this study was an exploration into the distinct features of text posted to NASA's Twitter site and the potential for these posts to serve as more engaging scientific text than traditional textbooks for adolescents. Results of the content analysis indicated the tweets and linked texts on the NASA Twitter site were constructed primarily as a form of "adapted primary literature" where science texts created by scientists for other scientists are presented in a slightly modified format for the general public. Further, the content analysis revealed the majority of text posted was designed to cultivate scientific knowledge for novices. Findings of the content analysis are presented and implications for teaching scientific literacies to adolescents using the social media site Twitter are discussed.